Building from gender experiences and learning for phase 2 of the CGIAR research programs - Pyburn, Rhiannon (International Livestock Research Institute, 2016)
The CGIAR research program has been doing capacity development of non-gender scientists on how to integrate gender in their work. An institutional architecture has also been built to support gender integration, for example, interdisciplinary teams with a gender-initiative representative on the program management committee, and the “gender tax” which allocates part of the project budget to gender research. A lot of learning has been brought into planning Phase 2 of the CGIAR research program. Examples are ways to systematize gender budgeting, ensuring that gender scientists are supported for the the time they allocate, and having their contribution reflected in the authorship of publications. Interview with Rhiannon Pyburn (Royal Tropical Institute) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684